Sewage sludge Composting Simulation as carbon / nitrogen concentration change - Kabbashi, Nassereldeen Ahmed (Elsevier BV, 2011)
Available composting models do not describe accurately the dynamics of composting processes. Difficulty in modeling composting processes is attributed mainly to the unpredicted change in process rate caused by change in activation energy value (E). This paper presents the results of an attempt made to utilize patterns of change in carbon, nitrogen and temperature profiles to model sewage sludge composting process as a multi-stage process. Results of controlled sewage sludge composting experiments were used in the study. All the experiments were carried out as batch experiments in a 300-liter Horizontal Drum Bioreactor (HDB). Analysis of the profiles of carbon, nitrogen and temperature has indicated that there are clear patterns that can be used to develop simple models of the process. It is found that change in the concentration of total carbon can reasonably be described by three constant process rates . It is found that the process starts with a certain process rate and continues with it until peak temperature is reached, then it reaches lower process in the declining phase of the thermophilic stage, and finally it proceeds with a faster process rate when maturation is reached. Change in the concentration of total nitrogen has shown to have the same patterns of change as carbon.